The influence of project-based learning models and creativity on critical thinking - K. Khairunnisa; Fauziyah Harahap; Ashar Ashairin (Inovasi Kurikulum, 2024)
Project-based learning offers alternatives that can potentially improve students' critical thinking skills. This study examines the effect of project-based learning models and creativity on the critical thinking of students in ecosystem learning in class V SDN Kaloy Tamiang Hulu Aceh Tamiang. The quantitative research approach uses the quasi-experimental method and the two-path ANAVA test. Based on the hypothesis testing, it is known that there is an influence of the project-based learning model on critical thinking skills with the results of analysis of variants of learning outcomes of students who learn to use the project-based learning model and have high creativity and students who have low creativity. Furthermore, the results of the variant analysis, the interaction between the Project-Based Learning Model and students' creativity and critical thinking students, show that groups of students with high creativity get a higher critical thinking value than those with low creativity tested for truth. There is an interaction between the Project-Based Learning Model on the creativity of students and critical thinking skills, as evidenced by the graph of the model interaction based on the results of the calculation between the Project-Based Learning Model on the creativity of students and the critical thinking skills of students in Class V SD Kaloy Tamiang Hulu Aceh Tamiang. AbstrakProject-based learning menawarkan alternatif yang berpotensi untuk meningkatkan kemampuan berpikir kritis peserta didik. Penelitian ini bertujuan untuk mengkaji pengaruh model project-based learning dan kreativitas terhadap berpikir kritis peserta didik dalam pembelajaran Ekosistem di kelas V SDN Kaloy Tamiang Hulu Aceh Tamiang. Pendekatan penelitian yakni kuantitatif dengan metode quasi eksperimen dan menggunakan uji ANAVA dua jalur. Berdasarkan uji hipotesis yang dilakukan diketahui bahwa terdapat pengaruh model project-based learning terhadap kemampuan berpikir kritis dengan hasil analisis varian hasil belajar peserta didik yang belajar menggunakan model project-based learning dan memiliki kreativitas tinggi serta peserta didik yang memiliki kreativitas rendah. Selanjutnya hasil analisis varian, interaksi antara model project-based learning dan kreativitas peserta didik terhadap berpikir kritis peserta didik menunjukkan kelompok peserta didik yang memiliki kreativitas tinggi memperoleh nilai berpikir kritis lebih tinggi dari kelompok peserta didik dengan kreativitas rendah teruji kebenarannya. Terdapat interaksi antara model project-based learning terhadap kreativitas peserta didik dan kemampuan berpikir kritis yang dibuktikan dengan grafik interaksi model berdasarkan hasil perhitungan antara model project-based learning terhadap kreativitas peserta didik dan kemampuan berpikir kritis IPA peserta didik kelas V SD Negeri Kaloy Tamiang Hulu Aceh Tamiang.Kata Kunci: berpikir kritis; kreativitas; pembelajaran berbasis proyek